Aqueous CO2 Reduction with High Efficiency Using α‐Co(OH)2‐Supported Atomic Ir Electrocatalysts. Issue 14 (27th February 2019) - Sun, Xiaofu; Chen, Chunjun; Liu, Shoujie; Hong, Song; Zhu, Qinggong; Qian, Qingli; Han, Buxing; Zhang, Jing; Zheng, Lirong
Abstract: Electrochemical reduction of CO2 into energy‐dense chemical feedstock and fuels provides an attractive pathway to sustainable energy storage and artificial carbon cycle. Herein, we report the first work to use atomic Ir electrocatalyst for CO2 reduction. By using α‐Co(OH)2 as the support, the faradaic efficiency of CO could reach 97.6 % with a turnover frequency (TOF) of 38290 h −1 in aqueous electrolyte, which is the highest TOF up to date. The electrochemical active area is 23.4‐times higher than Ir nanoparticles (2 nm), which is highly conductive and favors electron transfer from CO2 to its radical anion (CO2 .− ). Moreover, the more efficient stabilization of CO2 .− intermediate and easy charge transfer makes the atomic Ir electrocatalyst facilitate CO production. Hence, α‐Co(OH)2 ‐supported atomic Ir electrocatalysts show enhanced CO2 activity and stability. Abstract : High‐density atomic Ir supported on α‐Co(OH)2 had outstanding performance for CO2 reduction to CO. The faradaic efficiency can reach 97.6 % with a TOF of 38 290 h −1 . The high catalytic activity is attributed to more active sites for CO2 adsorption and activation and the higher efficiency in stabilizing the CO2 .− intermediate.